Carsten Höller : Production - Birnbaum, Danïel; KIASMA (Museum of Contemporary Art), Helsinki (Helsinki : KIASMA (Museum of Contemporary Art) Helsinki, 2000)
Production : a discussion between Daniel Birnbaum and Carsten Höller that took place in Stockholm ; the attempt to present the preparations for an exhibition Slides. To take away the exclusivity of the exhibits. to allow the other possibilities to have a voice as well. At the same time, to situate and explain the choice of the suggestion to be realized. As well as fundamentals of the decision and production.
Carsten Höller : Slides, KIASMA, Helsinki, 13.04. - 02.07.2000
keerdruk
Engels
Fins
boek
Keywords: Höller, Carsten